Legal Interventions for Elderly Care: Ensuring Social Welfare and Protection for Aging Populations - Somsack Sihaphom; Phonethip Chanthavong; Khamla Sombath (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This article investigates the role of legal frameworks in safeguarding the welfare of elderly populations, particularly in cases of financial abuse, healthcare, and elder neglect. By examining elderly care policies from various countries, the study evaluates the effectiveness of laws designed to protect the rights and dignity of older adults. Findings suggest that comprehensive elderly care policies, including legal protections and support systems, are essential for preventing abuse and ensuring quality of life.